Conducting and Insulating Materials - Bolotinha, Manuel (Neutro à Terra, 2016)
Conducting materials may be classified into three groups: conductors, semiconductors and imperfect insulators. This section will cover only conductors. In general, metals and alloys are conductors of electricity. The most common metals used in electricity are copper, aluminium and their alloys. The main electric characteristic of conductors is resistance that varies with temperature, presenting copper a lower resistance than aluminium.